Predictors of knowledge, attitudes and ever practice family planning among public secondary school teachers in Enugu east senatorial district, Nigeria - Nor Afiah, Mz; Okafor, Oc; Muthiah, Sg (Medknow Publications, 2022)
Background: Family planning deficiencies are responsible for high maternal, newborn, and child mortality in Nigeria, and more than half of all death among adult female is linked to maternal death.